Pembelajaran Daring dengan Model Kolaboratif 3CM dan Tutor Sebaya untuk Meningkatkan Hasil Belajar dan Kreativitas - Rida Larasanti; Erlina Prihatnani (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2021)
Design and application of learning models are important factors in achieving learning objectives. The purpose of this research is to apply online learning by collaborating the 3CM (Cool-Critical-Creative-Meaningful) model and peer tutors to improve learning outcomes and creativity of class IXA students of SMP Negeri 1 Batuwarno, applied for surface area of flat-sided shapes learning material. This Classroom Action Research uses the Kemmis & Mc Taggart model. The data collection techniques included documentation, observation, and test methods. The results showed that online learning using the collaboration of the 3CM learning model and peer tutors improved learning outcomes and creativity of class IXA students of SMP Negeri 1 Batuwarno. These results proved that the improvement of the learning process can still be done even though learning is carried out online, as long as it selects, prepares and implements the learning model appropriately.